Victims Are Not Guilty! Spiritual Abuse and Ecclesiastical Responsibility (MDPI, 2022)
The aim of this article is to show that victims of spiritual abuse are not guilty of what they have undergone and that, in the Catholic setting, the Church has an institutional responsibility for it. With this objective, after the Introduction (1), the paper analyses the definition of spiritual abuse (2); tackles several topics stemming from the analysis of definitions, such as the nature of spiritual power and its effects (3), the issue of vulnerability (4), the institutional dimension of spiritual abuse in the Catholic setting (5), and the disputed topic of intentionality (6). The article provides a conclusion that aims to summarize the results of the analysis (7).